A Green information technology governance framework for eco-environmental risk mitigation - Anthony Jr, Bokolo; Mazlina, Abdul Majid; Awanis, Romli (Inderscience Enterprises Ltd., 2017)

(untitled)
Over the years, information technology (IT) has changed IT practitioners’ behaviours profoundly and therefore has the potential to support the shift to a sustainable organisation. Sustainability has gradually become significant to IT industries as a response to the rapid reduction of natural resources. The role and contribution of IT to sustainability has become the concern of IT industries. Green IT has become one of the latest considerations to reduce energy consuming of IT operation. IT industries are adopting novel approaches towards Green practice adoption in their governance process, but their capability to mitigate environmental risk that occurs in IT Governance process in a sustainable approach has not been successfully applied, thus there is need to develop a Green IT governance framework that can assist in mitigating environmental risk in an eco-friendly manner. Findings from this paper show that the proposed framework can assist IT practitioners implement eco-environmental risk mitigation